Composition‐Dependent Hot Carrier Relaxation Dynamics in Cesium Lead Halide (CsPbX3, X=Br and I) Perovskite Nanocrystals. (20th March 2017) - Chung, Heejae; Jung, Seok Il; Kim, Hyo Jin; Cha, Wonhee; Sim, Eunji; Kim, Dongho; Koh, Weon‐Kyu; Kim, Jiwon
Abstract: Cesium‐based perovskite nanocrystals (NCs) have outstanding photophysical properties improving the performances of lighting devices. Fundamental studies on excitonic properties and hot‐carrier dynamics in perovskite NCs further suggest that these materials show higher efficiencies compared to the bulk form of perovskites. However, the relaxation rates and pathways of hot‐carriers are still being elucidated. By using ultrafast transient spectroscopy and calculating electronic band structures, we investigated the dependence of halide in Cs‐based perovskite (CsPbX3 with X=Br, I, or their mixtures) NCs on the hot‐carrier relaxation processes. All samples exhibit ultrafast (<0.6 ps) hot‐carrier relaxation dynamics with following order: CsPbBr3 (310 fs)>CsPbBr1.5 I1.5 (380 fs)>CsPbI3 NC (580 fs). These result accounts for a reduced light emission efficiency of CsPbI3 NC compared to CsPbBr3 NC.